Perencanaan Pembangunan Kepenghuluan Bagan Manunggal Kecamatan Bagan Sinembah Tahun 2013-2014 - Regina Ayu; Adlin (Nakhoda: Jurnal Ilmu Pemerintahan, 2015)
Background research problems. In the Rural Development Planning Meeting (Musrenbangdes) aims to accommodate all the aspirations of the community to set priorities according to the needs of community activities in order to overcome the existing problems. The program proposed in Musrenbangdes Chart Manunggal an elite formulation refresentasi only and not based on the level of the priorities and needs of the community so that there are many developments that communities need that should be included in the proposed development plan will be but is not recommended in the proposed development plan. And also the lack of participation of stakeholders and communities in the implementation and lack of socialization Musrenbangdes representatives of government agencies Kepenghuluan about Musrenbangdes. Success or failure in the implementation of Musrenbangdes, can be seen from the quality of Musrenbangdes as well as effective, efficient and keoptimalannya in Musrenbangdes implementation and the factors that affect the implementation of Musrenbangdes. The purpose of this research is known that in order to know the process of village development planning meeting (Musrenbangdes) chart Manunggal look of the stages Musrenbangdes and the factors that cause not suksenya development planning Kepenghuluan Chart Manunggal theoretical concepts used are as for the cause of weak governance capacity of villages in village development planning (Asmara Hadi 2001) and the factors that influence the process of preparing the development rencanan villages / wards (Raharjo Adisasmita). The method used is a method of qualitative research study conducted by the descriptive data in the data collection, research using interview techniques, documentation and literature studies using informants as sources of information. Results of this study, a portrait that from the results of the implementation of Musrenbangdes Chart Manunggal said not optimal and maximum efficiency and effectiveness has not been done so that the results Musrenbangdes priotitas not based on the scale and needs of the community at large so that actually perceived benefits and impacts positively by the public.